Factors Influencing Stroke Occurrence in Outpatient Patients in Bekasi District Hospital - Abdul Khamid; Arifah Rakhmawati (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: According to medical record data obtained from the Bekasi Regency Hospital, the number of stroke patients has increased in the last three years, with 1,721 people (1.52%) of the total number of patients as many as 112,925 people in 2016, 2,060 people (1.82%) out of a total of 113,240 patients in 2017, and 2,875 people (2.53%) out of a total of 113,728 patients in 2018. These statistics show that the incidence of stroke is increasing year after year. Methods : Analytic with a cross-sectional approach is used in the research procedure. All stroke patients who completed outpatient examinations at the Bekasi District Hospital in December 2018 were included in this study, with a total sample size of 103 persons (Systematic Random Sampling). Univariate and bivariate analysis with the chi square test are utilized as analytical methods. Result : The occurrence of stroke is a risk factor because the function of cells, tissues, and organs decreases with age as a natural process of aging. Influence is a common source of behavior problems in children and young people. The majority of stroke patients in this study were above the age of 55, accounting for 42.7% of all stroke patients. Estrogen plays a role in boosting HDL levels. With a vascular illness mechanism, hypertension frequently produces abnormalities in the function and structure of a person's brain. Conclusion: Each of the four variables has an effect on the occurrence of stroke. With a p value of 0.05, this indicates that age, gender, history of hypertension, and history of diabetes all have an impact on the incidence of stroke.